2022
DOI: 10.1073/pnas.2202487119
|View full text |Cite
|
Sign up to set email alerts
|

The structural origin of the efficient photochromism in natural minerals

Abstract: Significance Natural photochromic minerals have been reported by geologists for decades. However, the understanding of the photochromism mechanism has a key question still unanswered: What in their structure gives rise to the photochromism’s reversibility? By combining experimental and computational methods specifically developed to investigate this photochromism, this work provides the answer to this fundamental question. The specific crystal structure of these minerals allows an unusual motion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…To understand the origin of the additional reflectance side bands we recall two properties of the hackmanites structure reported before: (i) we have recently shown that sodium atoms can move from one b-cage to another (see the ESI † for more information about the structural details) during the UV tenebrescence process proving that these ions are mobile. 31 (ii) we also reported that under X-ray exposure, NaCl can exit from the hackmanite 5 generating Na and Cl vacancies. In other words, Na atoms can move inside the hackmanite and even exit the structure.…”
mentioning
confidence: 64%
“…To understand the origin of the additional reflectance side bands we recall two properties of the hackmanites structure reported before: (i) we have recently shown that sodium atoms can move from one b-cage to another (see the ESI † for more information about the structural details) during the UV tenebrescence process proving that these ions are mobile. 31 (ii) we also reported that under X-ray exposure, NaCl can exit from the hackmanite 5 generating Na and Cl vacancies. In other words, Na atoms can move inside the hackmanite and even exit the structure.…”
mentioning
confidence: 64%
“…Here, we can introduce the fact that our model a priori overestimates the bleaching energies (i.e., underestimates the metastability of the colored form) but reproduces qualitatively good experimental observations. 7 The calculations also show the possibility to slightly tune the bleaching energy (E b ) essentially by modifying the halogen atom. Indeed, whatever A (A = Al, Ga) and B (B = Si, Ge) in ABX's composition, (X = Cl, Br, I) we have…”
Section: àmentioning
confidence: 86%
“…The same methodology as the one reported here was actually used to simulate F-center's absorption in marialite and was able to quantitatively reproduce this red-shift. 7 In Fig. 7, we also report the absorption spectrum for a system with an additional sodium atom placed in the vicinity of the F-center (structure referred to as Na 5 ).…”
Section: àmentioning
confidence: 99%
See 2 more Smart Citations